Robin Williams' suicide: a case study - Tohid,Hassaan (2016)
Abstract Introduction: The world renowned comedian and four-time Oscar nominated actor Robin Williams died on August 11, 2014. From the outset, the news indicated that his death was believed to be a suicide and this was later confirmed to be true by the autopsy reports. Williams had been suffering from severe depression, which is believed to be the leading contributor to his suicide. In this case study, I will highlight the event of the actor's suicide and the main risk factors along with depression leading to his tragic death. As of the end of 2015, no other case study seemed to have addressed or explored the links between the cause (or causes) and events leading to Robin Williams' suicide. Case description: Robin Williams was suffering from relationship problems, financial problems, drug addiction, and major depression. All of these factors led to his suicide. Comments: The chances of committing suicide drastically increase in the presence of any of the key risk factors. Unfortunately, the actor Robin Williams was dealing with four of the major risk factors all together, which put him at a high risk of committing suicide and eventually led to his tragic death.